2007 IEEE Nuclear Science Symposium Conference Record 2007
DOI: 10.1109/nssmic.2007.4437134
|View full text |Cite
|
Sign up to set email alerts
|

GEANT4 simulation of an NSECT system for iron overload detection

Abstract: Hemochromatosis (iron overload in liver) is a condition that causes serious consequences for the patient through an increase in the body's iron stores. Diagnosis of the excess iron, which is often stored in the liver, requires an invasive biopsy. We are developing neutron stimulated emission computed tomography (NSECT) as a non-invasive alternative to measure liver iron concentration to diagnose hemochromatosis. This measurement is performed using an incident neutron beam that scatters inelastically with iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Applications in which mixed neutron and gamma-ray radiation fields are involved have gained steady interest through the years, especially in the areas of non-proliferation [1][2][3], radiography and tomography [4][5][6][7][8] and medical imaging [9]. Two approaches made it possible for these applications to succeed: scintillation materials sensitive to both radiation fields and multi-detector systems.…”
Section: Introductionmentioning
confidence: 99%
“…Applications in which mixed neutron and gamma-ray radiation fields are involved have gained steady interest through the years, especially in the areas of non-proliferation [1][2][3], radiography and tomography [4][5][6][7][8] and medical imaging [9]. Two approaches made it possible for these applications to succeed: scintillation materials sensitive to both radiation fields and multi-detector systems.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [1][2][3][4][5][6][7][8] we have described the development of neutron stimulated emission computed tomography (NSECT) as a non-invasive technique for quantitative measurement of iron in the human body. Using inelastic scatter spectroscopy, NSECT determines the iron concentration in a target organ by quantitative measurement of gamma radiation emitted from interactions between neutrons and iron nuclei in the organ.…”
Section: Introductionmentioning
confidence: 99%
“…These simulations have also been used to analyze detection accuracy and patient dose for different configurations of the NSECT system 7,8 . While the results of the simulation studies have demonstrated strong potential for iron overload detection through NSECT, in order for successful clinical translation of the technology it is imperative to analyze the sensitivity limit that can be achieved using currently available source and detector technology.…”
Section: Introductionmentioning
confidence: 99%